PEMANFAATAN KONSEP WAJAH DALAM FILM DEATH NOTE (2006) - Farhan Firdaus, Muhammad; Taqdir, Taqdir; Kasmawati, Kasmawati (Universitas Hasanuddin, 2021)
This study aims to classify the use concept of face in the film Death Note. This research is qualitative descriptive research. The data of this study is the speech in the film Death Note. Data collection is done with a note-checking technique. Data analysis techniques used in the form of data identification, understanding data, data classification, data analysis and concluding research results. The result of this study the concept of a more dominant positive face appeared is the category of